1958
DOI: 10.1139/z58-050
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Permeability, Diapause, and Hatching in the Eggs of the Mosquito Aedes Hexodontus Dyar

Abstract: Methods for collection in the laboratory of many thousands of eggs from field-collected, blood-fed females are described. Also a way of separating fertile from infertile eggs is outlined. When the eggs are laid they are white but begin to darken within one-half hour. The darkening did not occur when the egg cell or early embryo was killed.Two changes in permeability in the prediapause stage of the eggs of Aedcs hexodontus were observed. The first took place as the chorion changed from white to black. The egg l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…X-ray diffraction studies (Harwood, 1958). Histochemical tests suggested that a chitin-like component is a component of the shell (Beckel, 1958), but the presence of chitin has never been confirmed by other techniques. In addition, there is no agreement about the tissue source of the chitin-like component; some authors suggested that it is of embryonic origin (Harwood and Horsfall, 1959;Clements, 1992), while others have indicated that it is synthesized by ovarian follicular epithelial cells (Powell et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray diffraction studies (Harwood, 1958). Histochemical tests suggested that a chitin-like component is a component of the shell (Beckel, 1958), but the presence of chitin has never been confirmed by other techniques. In addition, there is no agreement about the tissue source of the chitin-like component; some authors suggested that it is of embryonic origin (Harwood and Horsfall, 1959;Clements, 1992), while others have indicated that it is synthesized by ovarian follicular epithelial cells (Powell et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that there is a chitin-like component present in mosquito eggshells (Beckel, 1958;Harwood and Horsfall, 1957;Harwood, 1958;Powell et al, 1986). There is no doubt that eggshells or egg coverings play an important role in the survival of mosquito species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulated that the few embryos that survive acquired enough water in hyaluronic acid to survive and hatch. Alternate mechanisms resulting in damage to embryogenesis would include decreased oxygen intake as a result of poorly developed aeropyles (Jones 1968, Mohinder 2001, as well as lack of a water-proofing wax layer that is part of the serosa cuticle (Beckel 1958, Christophers 1960, Clements 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Desiccation of the embryo begins shortly after the serosa cuticle is synthesized (Lazzaro-Rezende et al 2008). The serosa cuticle develops during embryogenesis and becomes the third layer of the egg shell, just beneath the endochorion (Beckel 1958, Clements 1996. Failure of egg adhesion after oviposition can prevent cuticle formation.…”
Section: Introductionmentioning
confidence: 99%